2016
DOI: 10.1177/1757975916658002
|View full text |Cite
|
Sign up to set email alerts
|

Association between parent and child weight status among private school children in Delhi, India

Abstract: Over the past three decades there has been a surge in the prevalence of overweight and obesity worldwide in both adults and children. To date few studies have examined obesity in India and most have only looked at prevalence estimates. While studies in Western countries have identified parent weight status as a predictor of child weight status, there have been no studies examining this association in India. This study examined the relationship between parent weight status and child weight status using an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…Children with obese and abdominal obese parents had significantly higher odds of having excess weight, obesity, abdominal obesity and elevated BP. These results are consistent with some previous studies [ 8 , 9 , 12 , 24 – 26 ]. A recent study on a large international sample from 12 countries reported positive associations between parental and child overweight as well as between parental education and child overweight.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Children with obese and abdominal obese parents had significantly higher odds of having excess weight, obesity, abdominal obesity and elevated BP. These results are consistent with some previous studies [ 8 , 9 , 12 , 24 – 26 ]. A recent study on a large international sample from 12 countries reported positive associations between parental and child overweight as well as between parental education and child overweight.…”
Section: Discussionsupporting
confidence: 94%
“…Although we did not analyze the relationship between parental and child weight status separately for mothers and fathers, some of previous studies reported that maternal adiposity correlated more strongly with children weight status than paternal adiposity [ 26 , 27 , 29 ]. However, it is shown that correlation between overweight/obese children-father pairs (odds ratio: 3.2, 95% CI: 1.5–6.8) was stronger than that of overweight/obese children mother pairs (odds ratio: 2.2, 95% CI: 1.2–3.9).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, placenta from obese women with a male fetus contain increased amounts of carbonyls and nitrotyrosine, and as a potential compensatory mechanism, these placenta have elevations in glutathione peroxidase and thioredoxin reductase activity. The collective findings from this latter study reveal that the placenta of males derived from lean mothers possess the greatest antioxidant activity, but such protective responses are abolished with maternal obesity, which may account for later adverse outcomes in sons, in particular those born to obese mothers (Bridgman et al, 2018; Greene‐Cramer et al, 2018).…”
Section: Introductionmentioning
confidence: 82%
“…There is no conclusive evidence that parents contribute equally to the risk of childhood overweight or obesity,35 although some studies suggest the maternal impact to be greater than the paternal. An Indian family study found only the maternal weight to be associated with child weight 36. Likewise, a Finnish study of 4788 mother–father–child trios found that maternal weight gain ≥8 kg was a significant predictor of adolescent overweight in both offspring genders 14.…”
Section: Discussionmentioning
confidence: 99%